Pelaksanaan Pemungutan Retribusi Parkir Di Kota Bajawa (International Forum of Researchers and Lecturers, 2023)
This research aims to find out how the implementation of parking retribution in Bajawa City and the supporting and inhibiting factors of parking retribution implementation. This research uses a descriptive qualitative approach with empirical legal research type. The data collection techniques in this research are observation, interview, and document study. The data analysis techniques used in this research are data reduction, data presentation, and conclusion drawing. The results showed that the implementation of parking levies in bajawa city is not good enough seen from the results of research on parking lots, parking rates, the work of parking attendants, and community responses regarding parking where the four aspects have not been implemented properly where parking lots are still narrow, parking attendant services have received a lot of criticism from the community Parking rates set by the Ngada Regency Government are correct but the results of the levy itself are still very dependent on whether or not visitors are busy. The work of the parking attendants is not optimal because the parking attendants on duty have never received special training, so the work of the parking attendants has received a lot of criticism from the community. Parking attendant services to parking service users are said to be ineffective and need to be improved. Supporting factors in the implementation of parking levy collection are joint operations and the role of mass media as a source of information for the community. The inhibiting factors in the implementation of parking levy collection are the emergence of illegal parking, lack of awareness of parking attendants and the public in traffic and inadequate parking facilities.